2013
DOI: 10.1177/1043454213504497
|View full text |Cite
|
Sign up to set email alerts
|

Helping the Helpers

Abstract: Burnout is a major problem in pediatric oncology staff. Mindfulness practices can be taught in the workplace and may be a useful component of a multidimensional strategy to reduce burnout in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
100
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 24 publications
0
100
1
4
Order By: Relevance
“…The hematology/oncology unit was still a positive predictor (β = +0.16) of job satisfaction and negative predictor (β = -0.22) of burnout. This is in contrast to the previous study results that nurses working in the hematology/oncology units have low job satisfaction, high burnout, and high levels of negative stress related to the intense psychological, emotional, and nursing care required to meet the needs of children with cancer as well as the needs of their families [5,23] .…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…The hematology/oncology unit was still a positive predictor (β = +0.16) of job satisfaction and negative predictor (β = -0.22) of burnout. This is in contrast to the previous study results that nurses working in the hematology/oncology units have low job satisfaction, high burnout, and high levels of negative stress related to the intense psychological, emotional, and nursing care required to meet the needs of children with cancer as well as the needs of their families [5,23] .…”
Section: Discussioncontrasting
confidence: 55%
“…Higher organizational support was reported by pediatric nurses in magnet hospitals compared to those in non-magnet hospitals [21] . Although a randomized control study among pediatric oncology nurses showed no significant improvement in their perceived stress or burnout after 8 weekly sessions of a mindfulness training program, they reported less stress, improved compassion, and better self-awareness in qualitative analysis [23] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other six studies had a small sample size that may affect the validity of the study and the results (Calisi, ; Klatt et al, ; Kubota et al, ; Moody et al, ; Singh & Jain, ; Yousefi et al, ). Two pilot studies were done out of ten studies (Calisi, ; Moody et al, ), one of them showed that there were no statistically significant differences between the two groups in terms of occupational stress (Moody et al, ). Due to the small sample size, the research outcomes could not be generalized to other population, increasing the likelihood of biased responses.…”
Section: Resultsmentioning
confidence: 99%
“…Stress management refers to the act of developing and implementing strategies or interventions for reducing or controlling occupational stress (Happell et al, ). A range of strategies and interventions has been used for stress management, for example, mindfulness training, massage intervention and yoga (Cutshall et al, ; Fang & Li, ; Moody et al, ; Pipe et al, ; Yousefi, Mirzamohamadi, & Nazari, ). These stress management techniques increase the employees’ ability to cope with stress and thereby safeguard their resources (Krölla, Doeblerb, & Nüescha, ).…”
Section: Introductionmentioning
confidence: 99%